Utilizing Picture Series to Boost Writing Ability of Upper-Secondary Students - Amelia, Rahma Rizqina; Nirmala, Nirna (EEdJ: English Education Journal, 2025)
This study aims to determine the effect of picture series on students' writing abilities and to determine their responses to the use of picture series in improving the ability to write recount texts in class X SMA Daarul Muttaqien 2 in the academic year 2022/2023. This study used quantitative methods with pre-experimental design. The samples used in this study were 48 students in the experimental class. Data were collected by using the test (pre-test and post-test) and questionnaire. Data analysis done by using Shapiro-Wilk showed the value of Asymp.Sig (2-tailed) was 0.000, less than 0.05. Therefore, it can be concluded that the working hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected. This means that the use of picture series had a significant effect on improving students' writing ability. The findings indicated that using the pictures series helped students improve writing ability, especially to decrease error rates of word placement. It made students more confident and enjoyed English writing texts due to the use of picture series as an effective medium in learning. As a result, it is advised for English teachers to choose relevant picture series to meet the objectives to improve students' writing abilities.